ESTIMATES OF METHANE OUTPUT FROM MUD EXTRUSIONS AT THE EROSIVE CONVERGENT MARGIN OFF COSTA RICA - Mau S.; Sahling H.; Rehder G.; Suess E.; Linke P.; Soeding E. (My University, 2006)
Four mud extrusions were investigated along the erosive subduction zone off Costa Rica. Active fluid seepage from these structures is indicated by chemosynthetic communities, authigenic carbonates and methane plumes in the water column. We estimate the methane output from the individual mud extrusions using two independent approaches. The first is based on the amount of CH 4 that becomes anaerobically oxidized in the sediment beneath areas covered by chemosynthetic communities, which ranges from 104 to 105 mol yr- 1. The remaining portion of CH4, which is released into the ocean, has been estimated to be 10 2-104 mol yr- 1 per mud extrusion. The second approach estimates the amount of CH4 discharging into the water column based on measurements of the near-bottom methane distribution and current velocities. This approach yields estimates between 104-10 5 mol yr-1. The discrepancy of the amount of CH 4 emitted into the bottom water derived from the two approaches hints to methane seepage that cannot be accounted for by faunal growth, e.g. focused fluid emission through channels in sediments and fractures in carbonates. Extrapolated over the 48 mud extrusions discovered off Costa Rica, we estimate a CH4 output of 20•106 mol yr- 1 from mud extrusions along this 350 km long section of the continental margin. These estimates of methane emissions at an erosional continental margin are considerably lower than those reported from mud extrusion at accretionary and passive margins. Almost half of the continental margins are described as non-accretionary. Assuming that the moderate emission of methane at the mud extrusions off Costa Rica are typical for this kind of setting, then global estimates of methane emissions from submarine mud extrusions, which are based on data of mud extrusions located at accretionary and passive continental margins, appear to be significantly too high. © 2005 Elsevier B.V. All rights reserved.
Keywords: CHEMOSYNTHETIC SPECIES; COSTA RICA FOREARC; METHANE OUTPUT; METHANE PLUME; MUD EXTRUSION